PEMBANGUNAN DESA DALAM TINJAUAN PEMIKIRAN WOOLCOCK DAN NARAYAN - Mulianto, Budi (UIR PRESS, 2017)
The purpose of this paper is to describe the role of social capital oriented to economic development through four approaches namely; communitarian approaches, networking approaches, institutional approaches and synergy approaches proposed by Woolcock and Narayan in his article Social Capital: Implications for Development Theory, Research, and Policy. Content analysis analysis on one concept presents a formula that there is an influence between social relations in development. Woolcock and Narayan revealed the phenomenon of development failure due to neglect of social relationships. If synergized in rural development, policy recommendations are formulated on the question of how social capital can affect the welfare of society, in the context of relations with the state as a party with great authority over the social development of rural communities. Summarizing what Woolcock and Narayan have to say, good government performance accompanied by strong social capital will be believed to bring about good economic and social prosperity.